A Conceptual Study of Dhatu Poshan Nyaya (Metabolic Transformation) in Ayurvedic Perspective - Verma, Priyanka; Nagar, Lalit Kumar; Sharma, Ashok Kumar; Sharma, Kishori Lal; Meena, Rekhraj (International Research Journal of Ayurveda & Yoga, 2023)
This review enlightens future research and scientific approach of Ayurveda in the context of Dhatu Poshna Nyaya (metabolic transformation and movement of substances through cell membrane). The things that truly support a living body are called dhatus. Dhatu denotes physical sustenance and food from the sole Sara component of the Ahara Rasa. A dietary substance’s metabolism refers to a set of particular biochemical reactions that take place inside a living thing from the time it is incorporated into a cell or tissue until it is excreted, some of which are associated with tissue synthesis and other metabolic processes. Those who break down tissue are said to be catabolic or anabolic, respectively. Numerous explanations have also been put out in the case of Dhatu Poshan. Numerous ideas have been developed regarding the process by which different nutrients are ingested by the body. One should consider all of these Nyayas comparable to one another.